Matthew P. Maher. The fortifications of Arkadian city states in the Classical and Hellenistic periods. - Müth, Silke (Journal of Greek Archaeology, 2019)
Matthew Maher’s monograph on the fortifications of Arkadian city states is (although not mentioned in the book) based on a PhD dissertation at the University of British Columbia (Vancouver) in 2012. It is a very welcome volume, because it supplies the growing interest in both the history and archaeology of Arkadia as a central Greek region and in ancient fortifications in a regional scope. As Maher writes in his introduction, he sees his study in the light of the ‘move away from traditional stereotypical interpretations of a poor and isolated Arkadia towards a view of a moderately prosperous region whose inhabitants generally followed the same patterns of social, political, and cultural development seen elsewhere in ancient Greece’ (p. 1) – a move that only can be appreciated.